Effect of Non Ionic Surfactant Addition to Cellulase Performance in High-Substrate-Loading-Hydrolysis of Palm Oil EFB and Water-Hyacinth - Teuku Beuna Bardant; Sudiyarmanto Sudiyarmanto; Haznan Abimanyu; Aisha Kania Hanum (Universitas Gadjah Mada, 2013)
Enzymatic hydrolysis with high substrate loading of palm oil (Elaeis guineensis) empty fruit bunch (EFB) and water-hyacinth (Eichhornia crassipes) were investigated as a prior part of ethanol production from lignocelluloses. Commercial surfactant Span 85 and Tween 20 were used as cellulase performance enhancer in hydrolysis process with substrate loading above 20% (w/w). Cellulase performances were compared based on hydrolysis conversion. Hydrolysis conversions of EFB using cellulase with concentration 10 and 15 FPU/g-substrate was 38.55% and 88.80% respectively. Addition 2% (v/v) of Tween 20 to EFB hydrolysis reaction with cellulase concentration 10 FPU/g-substrate gave the conversion 87.30%. This addition enhance the cellulase performance up to 226.5% or similar with the performance of cellulase 15 FPU/g substrate. Addition 2% (v/v) of Span 85 to the similar reaction only enhances cellulase performance to 174.7%. Hydrolysis conversion of boiling-pretreated water-hyacinth and autoclave-pretreated water-hyacinth using cellulase 15 FPU/g-substrate was 45.84% and 52.29% respectively. Addition 2% (v/v) of Tween 20 and Span 85 to boiling-pretreated water-hyacinth hydrolysis with cellulase concentration 15 FPU/g-substrate enhance cellulase performance of 128.9% and 153.5% respectively. Addition 1% (v/v) of Tween 20 and Span 85 to the similar reaction with cellulase concentration 10 FPU/g-substrate gave conversions 51.00% and 53.79% respectively, or similar with conversion of autoclave-pretreated water-hyacinth hydrolysis with 15 FPU/g-substrate.